EKSPLORASI REGULASI EMOSI MELALUI PENDEKATAN BIOMEKANIKA DALAM AKTIVITAS OLAHRAGA PERMAINAN PADA MAHASISWA PENDIDIKAN OLAHRAGA - Intan Kusuma Wardani; Kokom Supriyatnak; Tiassari Janjang Suminar (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2026)
This study aims to analyze the relationship between the body's biomechanical responses and emotional regulation of Physical Education students during game sports. Game sports not only demand physical skills but also trigger emotional responses due to competition, teamwork, and time pressure. This study used a mixed-methods design with an experimental observational approach. The subjects consisted of 40 Physical Education students participating in two game conditions: a competitive condition and a cooperative condition. Biomechanical data were collected through analysis of body posture and muscle activity using surface electromyography (EMG), while emotional regulation was measured using an anxiety and positive-negative affect questionnaire. The results showed that the competitive condition caused a significant increase in neck and shoulder muscle activity and a more rigid posture, which correlated with increased anxiety. Conversely, the cooperative condition showed a more relaxed posture pattern and improved emotional regulation. These findings confirm that the body's biomechanical responses are closely related to students' emotional regulation during game sports. This study is novel in its integration of biomechanical analysis and emotional regulation within the context of physical education.